Neutralization against Omicron sublineages (BA.2/BA.5/BQ.1.1/XBB/XBB.1.5) in bivalent BNT162b2-vaccinated HCWs with or without risk factors, or following BT infection with Omicron - Amano, Masayuki; Otsu, Sachiko; Uemura, Yukari; Ichikawa, Yasuko; Matsumoto, Shota; Higashi-Kuwata, Nobuyo; Matsushita, Shuzo; Shimada, Shinya; Mitsuya, Hiroaki (Scientific reports, 2023)
SARS-CoV-2-BA.4/5-adapted-bivalent-BNT162b2-vaccine ( bv BNT), developed in response to the recent emergence of immune-evasive Omicron-variants, has been given to individuals who completed at least 2-doses of the monovalent-BNT162b2-vaccine ( mv BNT). In the present cohort study, we evaluated neutralization-titers (NT 50 s) against Wuhan-strain (SCoV2 Wuhan ) and Omicron-sublineages including BA.2/BA.5/BQ.1.1/XBB/XBB.1.5, and vaccine-elicited S1-binding-IgG in sera from participants-vaccinated with 5th- bv BNT following 4th- mv BNT. The 5th- bv BNT-dose elicited good protective-activity against SCoV2 Wuhan with geometric-mean (gMean)-NT 50 of 1966–2091, higher than the peak-values post-4th- mv BNT with no statistical significance, and favorable neutralization-activity against not only BA.5 but also BA.2, with ~ 3.2-/~ 2.2-fold greater gMean-NT 50 compared to the peak-values post-4th- mv BNT-dose, in participants with or without risk factors. However, neutralization-activity of sera post-5th- bv BNT-dose was low against BQ.1.1/XBB/XBB.1.5. Interestingly, participants receiving bv BNT following breakthrough (BT) infection during Omicron-wave had significantly enhanced neutralization-activity against SCoV2 Wuhan /BA.2/BA.5 with ~ 4.6-/~ 6.3-/~ 8.1-fold greater gMean-NT 50 , respectively, compared to uninfected participants receiving bv BNT. Sera from BT-infected-participants receiving bv BNT had enhanced neutralization-activity against BQ.1.1/XBB/XBB.1.5 by ~ 3.8-fold compared to those from the same participants post-4th- mv BNT-dose, and had enhanced gMean-NT 50 ~ 5.4-fold greater compared to those of uninfected-participants’ sera post- bv BNT. These results suggest that repeated stimulation brought about by exposure to BA.5’s-Spike elicit favorable cross-neutralization-activity against various SARS-CoV-2-variants.